2021
DOI: 10.1021/acs.jafc.1c04481
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Promotes Skeletal Muscle Fiber Remodeling by the AdipoR1-APPL1-AMPK Signaling Pathway

Abstract: Naringin, a natural flavonoid mainly found in citrus fruit, has been reported to exert a positive effect on improving skeletal muscle health. However, the effects and potential mechanisms of naringin on skeletal muscle fiber switching is still unclear. Here, we discovered that oral administration of naringin increased the low-speed running time, four-limb hanging time, body oxygen consumption in mice, enhanced aerobic enzyme activity, MyHC I expression, and slow-twitch fiber percentage in mice skeletal muscle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…40 Higher expression levels of MYH1, MYH2a, and MYH7b have been linked to increased muscle strength and mass, thereby achieving the purpose of enhancing skeletal muscle function and quality. 41 Moreover, polyphenol supplementation could increase the expression levels of MYH1 and MYH2a and thereby increase the proportion of type I and IIA fibers in mice. 42,43 In the present study, we found that the expression levels of MYH1, MYH2a, and MYH7b were significantly higher in the PUN group than in the HFD group, suggesting that PUN could increase the proportion of type I and IIA fibers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…40 Higher expression levels of MYH1, MYH2a, and MYH7b have been linked to increased muscle strength and mass, thereby achieving the purpose of enhancing skeletal muscle function and quality. 41 Moreover, polyphenol supplementation could increase the expression levels of MYH1 and MYH2a and thereby increase the proportion of type I and IIA fibers in mice. 42,43 In the present study, we found that the expression levels of MYH1, MYH2a, and MYH7b were significantly higher in the PUN group than in the HFD group, suggesting that PUN could increase the proportion of type I and IIA fibers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that DFS might be an alternative therapeutic agent for preventing and managing muscle atrophy. Recent studies have reported that natural compounds from plants such as resveratrol, naringin, and myricetin mediate muscle fiber transformation from slow-to-fast fiber type or vice versa 8 , 9 , 10 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The low-speed and high-speed running tests were carried out as described in previous studies. 29,30 The velocity of each group mice in high-speed test was increased by 5 m/min until 40 m/ min (every 2 min) and the velocity in low-speed test was increased by 1 m/min until 40 m/min (every 3 min).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Briefly, after 24 h acclimation of the system, the physical activity of mice was evaluated over the next 48 h by measuring the running or movements in the X -, Y - and Z -axes of metabolic chamber. , Mice’s muscle strength and exercise ability were tested by using the rat/mouse grip strength meter (SA417, Jiangsu Science Biotechnology Co., Ltd., Jiangsu, China) and treadmill (ZH-PT, KaiHuiSD Technology Co., Ltd., Beijing, China). The low-speed and high-speed running tests were carried out as described in previous studies. , The velocity of each group mice in high-speed test was increased by 5 m/min until 40 m/min (every 2 min) and the velocity in low-speed test was increased by 1 m/min until 40 m/min (every 3 min).…”
Section: Materials and Methodsmentioning
confidence: 99%